Kemampuan number sense mahasiswa calon guru matematika: Adakah komponen yang kurang dikuasai? - Nourma Pramestie Wulandari; Junaidi Junaidi (Mandalika Mathematics and Educations Journal, 2023)
Number sense is important to be mastered by a prospective mathematics teacher as a basis for learning mathematics and makes it easier to train students' flexibility in solving math problems related to numbers. However, the results of preliminary studies show that there are indications that the prospective teacher's ability to operate numbers is not good enough. This study uses quantitative methods that aim to investigate the number sense component of mathematics teacher candidates who are still weak. The respondents involved in this study were 36 students who were prospective third-year mathematics teachers who had taken linear algebra courses. The instrument used is a 30-item number sense problem developed based on the number sense component, namely understanding and skills about numbers, understanding and skills using number operations, and applying number skills and operations in computing. This number sense test is done for 30 minutes. The results showed that the number sense ability of prospective mathematics teacher students was average with an average percentage of correct answers of only 51.57%. The third component in number sense is the weakest mastered with a percentage of correct answers of only 46.39%.